Hart to Hart : The Complete First Season Disc 3 - Mankiewicz, Tom.; Robert Wagner; Stefanie Powers; Lionel Stander; Gregory J Barnett; Lee Bryant; Tara Buckman; Don Dandridge; Clifton James; Art Kassul; David Landsberg; Michael Lerner; et al. (USA Columbia Pictures Television, 1979)
A pilot film for a series which officially debuted a few days earlier. Robert Wagner and Stephanie Powers play the wealthy, happy married couple Jonathan and Jennifer Hart. He's a self made millionaire, CEO, she's a journalist; together they solve crimes. In this first escapade, the Harts tackle the case of a friend's death at a fancy health spa.
Languages : English, French Subtitles : English, German, French, Spanish, Italian
Keywords: Adventure; Crime -- Tv Series